(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article deals with the creation of water engines for mobile micro-hydroelectric power plants and pumps with a capacity of 1-10 kW, operating at the expense of the energy of naturally flowing water, i.e. development of methods of using the energy of flowing water, without the construction of hydraulic structures and dams, without causing harm to the environment. Also, an experimental model of a water engine and the results of experimental studies are presented.